2021
DOI: 10.21744/irjmis.v8n2.1325
|View full text |Cite
|
Sign up to set email alerts
|

development strategy of civil association cooperative

Abstract: Cooperatives' existence and role in supporting national economic activities are essential and strategic. Strengthening the cooperative economy and small business economy is a priority. Kediri City received the cooperative award from the Ministry of Cooperatives and MSME in 2017. The award was given because it successfully guided and developed Cooperatives. Until now Kediri City has a cooperative citizen association (CA) that has been formed. One hundred fifty cooperatives from a total of 352 CA have been creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Based on the findings, the study reported that eHealth framework of Saudi Arabia has been lacking few important aspects like data management, awareness creation among public, decreasing access and reachability etc. As per the reports of Areej AlFattani et al 33 Saudi Arabia's response to COVID-19 could provide a paradigm for better practices in dealing with the COVID-19 pandemic. The country took the WHO-recommended "whole-government" approach to controlling the COVID-19 pandemic.…”
Section: Management Of Resources In Healthcare Unitsmentioning
confidence: 90%
“…Based on the findings, the study reported that eHealth framework of Saudi Arabia has been lacking few important aspects like data management, awareness creation among public, decreasing access and reachability etc. As per the reports of Areej AlFattani et al 33 Saudi Arabia's response to COVID-19 could provide a paradigm for better practices in dealing with the COVID-19 pandemic. The country took the WHO-recommended "whole-government" approach to controlling the COVID-19 pandemic.…”
Section: Management Of Resources In Healthcare Unitsmentioning
confidence: 90%
“…This review utilized essential and auxiliary information hotspots for information assortment through perception, conveying polls, and documentation (de Villiers et al, 2014;Labuschagne et al, 2005). The primary data is presented through analysis using the Structural Equation Model Partial Square with several steps that develop the evaluation model by playing several tests clearly to get Convergent Validity Distinguishing validity and reliability and extractive variation and Cronbach Alpha which composes a structural model with determinant coefficient tests (Rahmiyati et al, 2021;Amerta et al, 2018). Tests the relevance of the perspective from there; the data is then tested to obtain the relevance of the overall structure model validation coefficient with the goodness of fit index.…”
Section: Methodsmentioning
confidence: 99%